Development of a Natural Chewing Gum from Plant Based Polymer - Palabiyik, Ibrahim; Toker, Omer Said; Konar, Nevzat; Oner, Baris; Demirci, Ahmet Sukru (SPRINGER/PLENUM PUBLISHERS, 2018)
In this study, Kenger gum obtained from Kenger plant (Gundelia tournefortii) was used in the production of biodegradable and edible chewing gum. Kenger gum was able to be softened by thermal process to improve its textural properties. 80% methanolic extract of gum showed 195.6 gallic acid equivalents (GAE) mg/100 g gum antioxidant activity and 17.9 mm inhibition zone for Escherichia coli O157:H7 as an antimicrobial activity. Softened Kenger gum was also characterized by texture properties, scanning electron microscope (SEM) images and chemical compositions. Hardness value of gum decreased from 864 to 238 g which was comparable to commercial chewing gums. Softened Kenger gum was observed to be a perfect substitute for a synthetic gum base in the production of a conventional chewing gum. Moreover, resilience value was remarkably found to be the best standard parameter to select chewing gums with desired textural properties.
Keywords: Kenger gum; Antioxidant activity; Antimicrobial activity; Textural properties; GUNDELIA-TOURNEFORTII L.; IN-VITRO; EXTRACTS; Engineering; Polymer Science